The economy structure – focus for education/science reforms in Ukraine - Svitlana Hlushchenko (Наукові записки НаУКМА: Економічні науки)
The article is about the reasoning importance and necessity of harmonizing the goals and methods of development and reform of education/science in Ukraine with development of priority economic sectors in Ukraine, including fixing the education and science (as an element of the knowledge economy) as priorities sectors in the structure of the Ukrainian economy. The author characterized indicators of Ukrainian economics development by type of: economics activity, capital investments, turnover of industrial enterprises, employment of population. All these characteristics show that in the last decades, the scientific and technical sectors of industry, according to most characteristics, occupied the smallest share in the structure of the Ukrainian economy. However, the sectors of wholesale and retail trade, the agricultural sector and the raw material sectors of industry had actively developed in Ukraine. Also, the author pays attention to the problems in education and science in Ukraine: to respect and demand for these professions in the Ukrainian society and to financing support. Reforms and support of education/science must be harmonized with the economic structure of Ukraine. They must be fixed on priority sectors for economic development. The education/science must be fixed as priority sectors like elements of the knowledge economy. The goals and objectives, the internal reforms and development in education/science must be oriented to the needs of the structure of the Ukrainian economy. Implementation of these steps will help improve the quality of educational and scientific activities, the effect of their impact on economic development in Ukraine, and the competitiveness of the Ukrainian state like knowledge economy will grow.